2022
DOI: 10.1177/21582440221138814
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Challenges for a Sustainable Community-Based Ecotourism: A Case Study of Rural Community in Sabah, North of Borneo

Abstract: COVID-19 has impacted the ecotourism industry significantly. It is imperative to examine and identify the key challenges in running rural ecotourism businesses to comprehend the mindset of the working community members before re-establishing a business model during endemic phase. This study aimed to explore and identify the resources and capabilities challenges perceived by the members of community-based ecotourism located in Marakau Village, Sabah. The study, which took place in 2021, employed a qualitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Their adaptive strategies included diversifying offerings, leveraging local resources, and integrating technology like virtual engagements and online promotions [ 30 ]. The study in Marakau Village, Sabah, North of Borneo founded that successful post-COVID-19 management of community-based ecotourism necessitates a holistic approach, encompassing human and natural resource management, strategic planning, collaboration, and adaptability for sustainability and success [ 31 ]. The study in CBT of the Andaman Coast of Thailand showed that key measures addressed included the characteristics of vaccinated tourists, ensuring community readiness by regularly checking service staff for COVID-19, implementing renovations, and designing pandemic-appropriate tourism activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their adaptive strategies included diversifying offerings, leveraging local resources, and integrating technology like virtual engagements and online promotions [ 30 ]. The study in Marakau Village, Sabah, North of Borneo founded that successful post-COVID-19 management of community-based ecotourism necessitates a holistic approach, encompassing human and natural resource management, strategic planning, collaboration, and adaptability for sustainability and success [ 31 ]. The study in CBT of the Andaman Coast of Thailand showed that key measures addressed included the characteristics of vaccinated tourists, ensuring community readiness by regularly checking service staff for COVID-19, implementing renovations, and designing pandemic-appropriate tourism activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Malaysia stands out for its rich marine resources and wide cultural diversity, making it an exceptional ecotourism destination that has fostered conservation, economic growth, and the quality of life of the local community [75]. Community-based ecotourism in Malaysia has been consolidated through homestay programs with local families, which have boomed since the 1990s, attracting millions of tourists from around the world who want to experience the local culture and exceptional biodiversity up close [76]. On the other hand, Thailand has had various sustainable political projects since 1980 that have allowed the creation of initiatives such as the National Ecotourism Action Plan, the Cooperative Ecotourism Network, the Thai Ecotourism Association, and the Foundation for Environmental Protection and Tourism, from which various community-based ecotourism proposals have emerged [77].…”
Section: Most Productive Countries and Most Studied Countriesmentioning
confidence: 99%
“…Until today there is no study that has compared the condition of natural resources before and after a pandemic, so this study would be the first of its type. [ 53 ] study on sustainable rural community-based ecotourism in Sabah, Borneo, is the closest study to quote during the pandemic.…”
Section: Introductionmentioning
confidence: 99%